Strategic of Entrepreneurship Retail Business Sector in Bogor City - Azizka, Intan; Kartika, Lindawati (Indonesian Journal of Business and Entrepreneurship, 2021)
Retail growth as one of the most important distribution chains in the product distribution cycle is a great opportunity for retail businesses. On the other hand, retail growth also brings increasing business competition, so it needs strategic planning. One method that can be used is strategic entrepreneurship which combines two theories, namely strategic management and entrepreneurship to maximize opportunities by creating competitiveness in business processes. This study aims to analyze the characteristic of the retail business sector in Bogor City, strategic entrepreneurial factors and the influence between Input-Process-Output segmentation using descriptive analysis methods and Structural Equation Modeling - Partial Least Square (SEM-PLS). The type of data used in this research is quantitative by using primary data in the form of interviews and filling out questionnaires and secondary data using literature studies and previous research. This research was conducted from December 2019 to May 2020 with a total of 85 retail respondents. The results showed that modern retail in the city of Bogor is included in starting a business and dominated by incorporated company. Retail in Bogor City is also dominated by women as top management and senior high school graduates. There were 6 strategic entrepreneurial factors namely environmental factors, organization resources, individual resources, resource orchestration, consumer value and competitive advantages, creating wealth and other benefits. The variables that have a positive and most significant influence were consumer value and competitive advantages. Variables that did not have a significant effect is individual resources. Keywords: descriptive analysis, input-proses-output, retail, sem-pls, strategic entrepreneurship